Revision of the Afrotropical species of Norbanus Walker (Hymenoptera: Pteromalidae) - Mitroiu, Mircea-Dan (Zootaxa, 2015)
The Afrotropical species of Norbanus Walker, 1843 (Hymenoptera: Pteromalidae) are revised. Four previously described Afrotropical species are recognized as valid and redescribed: N. africanus Subba Rao, 1973, N. garouae (Risbec, 1956) comb. nov. (transferred from Bruchobius Ashmead), N. kitegaensis (Risbec, 1957) and N. seyrigi (Risbec, 1952) comb. nov. (from Habrocytus Thomson). In addition, the Mediterranean species N. tenuicornis Bouček, 1970 is recorded for the first time from the Afrotropical region, and 21 species are described as new: N. aequus sp. nov., N. awi sp. nov., N. brevicephalus sp. nov., N. breviclava sp. nov., N. caloramans sp. nov., N. draco sp. nov., N. erebus sp. nov., N. foritempus sp. nov., N. gibber sp. nov., N. gracilis sp. nov., N. incombo sp. nov., N. ingens sp. nov., N. longissimus sp. nov., N. maliarphae sp. nov., N. mustatai sp. nov., N. pilosus sp. nov., N. pleuralis sp. nov., N. polaszeki sp. nov., N. prinslooi sp. nov., N. rotundus sp. nov., and N. sunabron sp. nov. Three extralimital species from North Africa are included in the key: N. cerasiops (Masi, 1922), N. guyoni (Giraud, 1869), and N. obscurus (Masi, 1922). Lectotypes are designated for N. cerasiops, N. kitegaensis and N. seyrigi. The subgenus Picroscytoides Masi is placed in synonymy with Norbanus s.s. syn. nov. Host records are given for several new species, including some economically important pests of maize, sorghum or rice.